PERENCANAAN KETENAGAAN DALAM PERSPEKTIF MANAJEMEN PENDIDIKAN ISLAM - Amin, Sagir M. (Institut Agama Islam Negeri (IAIN) Palu, 2007)
To earn a good quality of Islamic education, a planner should perform a good planning. Planning will be helpful to the planner in directing his managerial objectives. In fact, planning can determine the profile of an organization that can make it professional. Besides, vision and mission of an organization can be well performed through a good planning.Â It is within this context that to enhance the quality of Islamic education, a planner should commit to the principles of planning.Kata Kunci: Perencanaan ketenagaan, manajemen pendidikan Islam